A structured light solution for detecting scapular dyskinesis - Verster, Jaco (Department of Human Biology, 2019)
Scapular dyskinesis is a common occurrence in overhead athletes, i.e. athletes who participate in any sport where the upper arm and shoulder is used above the athlete’s head. However, no consensus has been reached on how to evaluate scapular dyskinesis quantitatively. In this thesis, we developed a measuring tool that can be used to evaluate certain key clinical parameters specific to scapular dyskinesis. The tool employs a 3D structured light computer vision approach to create a surface map of the soft-tissue across the scapula. This surface map is then analysed using surface curvature analysis techniques to identify the key clinical parameters associated with scapular dyskinesis. The main advantage of this method is that it provides a measurement tool that may facilitate future quantitative analysis of these key parameters. This may aid with diagnosis and monitoring of the condition by allowing measurement data to be collected both before and after treatment and rehabilitation. We expect that this tool will make the monitoring of treatment effectiveness easier while contributing to diagnostic computer vision.